Pharmacological correction of intrarenal hemodynamic disorders in acute kidney injury (part 2) - Katherine K. Shramenko; Georgiy A. Gorodnik; Valentina P. Shano; Irina V. Kuznetsova; Aleksandr P. Grigorenko; Vladimir V. Potapov (Belgorod National Research University, 2018)
Introduction: Treatment of acute kidney injury (AKI) is a complex current problem. Mortality in this pathology is over 50%. One of the areas of correction therapy in AKI patients is the improvement of diagnostics and the earliest identification of the underlying cause of AKI. The second promising direction in reducing mortality is prevention of AKI progression (nephroprotection) and resulting multi-organ disorders by individual pharmacological and non-pharmacological intensive therapy. Objectives: to evaluate the possibilities of individual pharmacological correction and intensive care of patients with AKI of different origin. Materials and methods: A prospective nonrandomized study. Inclusion criteria: patients with prerenal, renal and subrenal AKI module in stage of oligoanuria and restoration of diuresis. Exclusion criteria: AKI in patients after cardiosurgery and operations on large vessels. Individual pharmacological and non-pharmacological correction (renoprotection) was performed in 250 ICU patients with prerenal (130), renal (81) and subrenal (39) AKI. The effectiveness of individual nephroprotection was assessed by the duration of the oligoanuria stage (indicator of AKI severity). Results and discussion: The basis of intensive therapy in AKI patients was renal replacement therapy and peridialysis care. Peridialisys support was presented by a complex of therapeutic measures aimed at preventing the progression of AKI (nephroprotection) and the prevention of multi-organ complications. Individual pharmacological and non-pharmacological peridialysis intensive therapy was performed, including: removal of the main cause of forming AKI; maintenance of normal circulation blood volume and effective cardiac output; maintenance of adequate lung ventilation (correction of hypoxia, timely ventilation); correction of hypertension, hypotension, and clinically significant arrhythmia; improvement of renal blood flow and stimulation of diuresis; stopping bleeding and correction of anemia; targeted antibiotic therapy; removal or adequate drainage of the intoxication focus (purulent focus); use of alternative ways of detoxication and efferent methods. It was proved that individual pharmacological and non-pharmacological nephroprotection made it possible to improve the results of treatment. The duration of the oligoanuria stage significantly (p < 0.05) decreased to 14.3±0.9 days in the main group (22.6±1.2 days in the comparison group). Conclusions: The medical technology of individual intensive therapy with renal replacement therapy and peridialysis care has been developed, including: a diagnostic stage with determination of peculiarities of renal hemodynamic disorders and pharmacological and instrumental (stenting, drainage, etc.) correction of the real cause and manifestations of AKI. Improving AKI diagnostics and carrying out individual pharmacological and non-pharmacological correction improves the results of AKI treatment.